Effect of Board Type on Some Properties of Bamboo Strandboard - Ihak Sumardi; Shigehiko Suzuki; Noor Rahmawati (Institute for Research and Community Services (LPPM) ITB, 2015)
The objective of this study was to evaluate the properties of bamboo strandboard (OSB) by comparing different board types and strand-lengths. Bamboo strandboards with nominal dimensions of 37 mm by 37 mm by 12 mm and target density 0.65 g/cm3 were manufactured using moso bamboo (Pyllostachys pubescent Mezel) and MDI resin to produce two types of strandlength. Two types of strand length and MDI resin were used to produce three types of strandboard. The bending properties and dimensional stability of the strandboards were evaluated according to the Japanese Industrial Standard (JIS) for particleboard. The results of this experiment indicate that the bending properties and internal bond strength were affected by both board type and strand-length. The distribution of resin inside the 80 mm strandboard was less homogenous than in the 50 mm strandboard, which affects the internal bond strength. Thickness swelling of the RAND board was the highest and linear stability was affected substantially by strand alignment. The RAND board and cross-oriented 3LAY board effectively restrained linear expansion in the direction perpendicular to the strand alignment. A cross-oriented core may be the most effective way to reduce dimensional change and bending property values in perpendicular directions.